Editorial November 2025 - Peace, Christopher (New Zealand Journal of Health and Safety Practice, 2025)
In this edition we mark 15 years since the Pike River mine disaster killed 29 men. We passed through the initial shock and anger to a promised land of new and more effective legislation and a new regulator. Unfortunately, the necessary regulatory system to underpin the new Act was not delivered under previous governments and our current government wishes to “reform” the incomplete system to deliver less enforcement, more advisory services by WorkSafe and more self-regulation. For a full picture of where we have gone wrong read the thoroughly researched and eloquent article by Rebecca Macfie (2025) in the New Zealand Listener of 15 November 2025.